USM LECTURER RECEIVES L'OREAL-UNESCO FOR WOMEN IN SCIENCE NATIONAL FELLOWSHIP RESEARCH GRANT WORTH RM30,000 FOR CANCER RESEARCH - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 9 October 2015 Universiti Sains Malaysia (USM) further strengthened its standing as a Research University when one of its lecturers received the L'orealUNESCO for Women in Science National Fellowship research grant worth RM30,000.